Production of Prednisolone by Pseudomonas oleovorans Cells Incorporated Into PVP/PEO Radiation Crosslinked Hydrogels. Issue 4 (30th September 2004) - Abd El-Hady, Abeer; Abd El-Rehim, Hassan A.
Abstract : In order to rise the yield of prednisolone from hydrocortisone, the Pseudomonas oleovorans cells were entrapped into radiation crosslinked poly (vinyl pyrrolidone)/poly(ethylene oxide) (PVP/PEO) hydrogel of different gel contents. The factors affecting the gel content and swelling behavior of the polymeric gel, such as polymer composition, polymer blend concentration, and irradiation doses, were investigated. The formation of gels having a good strength with the ability to retain a desirable amount of water in their three-dimensional network can be achieved by using PVP/PEO copolymer of composition( 90 : 10 ) and concentration of 15% prepared at 20 kGy irradiation dose. At these conditions the prepared hydrogel is considered the most favorable one that gave the highest hydrocortisone bioconversion and prednisolone yield, 81% and 62.8%, respectively. The improvement of prednisolone yield was also achieved by increasing substrate concentration. Maximum hydrocortisone bioconversion (86.44) was obtained at 18 hours by using substrate concentration of 30 mg. Reusability of immobilized Pseudomonas oleovorans entrapped into PVP/PEO copolymer hydrogel was studied. The results indicated that the transformation capacity of hydrocortisone to prednisolone highly increased by the repeated use of copolymer for 4 times. This was accompanied by an increase in prednisolone yield to 89% and the bioconversion of hydrocortisone was 98.8%.